Evaluation of Light Distribution and the Penetration Depth under Isometric Studies using fNIRS - Halim, A.A.A.; Laili, M.H.; Rusop, M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Functional near-infrared spectroscopy (fNIRS) has been widely used to solve the propagation of light inside the tissues and to quantify the oxygenation level of hemoglobin and myoglobin in human muscle. Penetration depth is one of the highlighted optical properties in this instrument in order to make sure light can be penetrated into deep human tissue layers. In this paper, our ultimate aim is to measure the penetration depth of muscle under different oxygenation states of isometric assessment in human using fNIRS. 27 sedentary healthy volunteers participated in this study. The result showed that, after all assessments, the mean signal of 3.0 and 4.0 cm distance of penetration depth showed more significant value detection (p≤0.05) measured by fNIRS. In addition, deoxygenated (p=0.031) show more significant in gender analysis compare to the oxygenated and total of hemoglobin and myoglobin. Thus, this result may help us to prove that our human muscle is transparent to this near infrared region and might be a useful tool for detecting oxygen status in muscle from living people either athletes or working people.